The association between coronary graft patency and clinical status in patients with coronary artery disease. (8th March 2021) - Gaudino, Mario; Di Franco, Antonino; Bhatt, Deepak L; Alexander, John H; Abbate, Antonio; Azzalini, Lorenzo; Sandner, Sigrid; Sharma, Garima; Rao, Sunil V; Crea, Filippo; Fremes, Stephen E; Bangalore, Sripal
Abstract: The concept of a direct association between coronary graft patency and clinical status is generally accepted. However, the relationship is more complex and variable than usually thought. Key issues are the lack of a common definition of graft occlusion and of a standardized imaging protocol for patients undergoing coronary bypass surgery. Factors like the type of graft, the timing of the occlusion, and the amount of myocardium at risk, as well as baseline patients' characteristics, modulate the patency-to-clinical status association. Available evidence suggests that graft occlusion is more often associated with non-fatal events rather than death. Also, graft failure due to competitive flow is generally a benign event, while graft occlusion in a graft-dependent circulation is associated with clinical symptoms. In this systematic review, we summarize the evidence on the association between graft status and clinical outcomes. Graphical Abstract: